“WHY ARE WE TO SHUT UP THE BOOK WEEPING?”: ELIZABETH GASKELL’S RUTH AND THE (IM)POSSIBILITY OF REDEMPTION FOR THE FALLEN WOMAN - Simionato, Deborah Mondadori (Organon, 2018)
Victorian literature is filled with images of women who have sinned, but often these characters are in the background, foreshadowing the heroine’s future if she is not proper and pious. Elizabeth Gaskell’s Ruth, however, puts the fallen woman in its centre and calls her its heroine. This paper aims to look at the contradictions imposed on middle-class women’s existence in the nineteenth century, especially concerning the figures of the Angel in the House and the fallen woman, which are essential for the analysis of Ruth and its tragic ending, in order to understand the (im)possibility of redemption for women in the Victorian period. Scholars such as Mary Poovey (1998) and Eleonore Davidoff (1995), amongst others, will provide the historical and sociological background necessary to this reading of Elizabeth Gaskell’s 1835 novel Ruth. KEYWORDS: Ruth; Elizabeth Gaskell; Angel in the House; Fallen Woman.